Boosting Global Customer Loyalty through E-CRM and Digital Marketing Strategies: Meningkatkan Loyalitas Pelanggan Global melalui E-CRM dan Strategi Pemasaran Digital - Nurcayani, Amaliasari; Sriyono, Sriyono (Indonesian Journal of Innovation Studies, 2024)
This study delves into the impact of electronic customer relationship management (e-CRM) and digital marketing on customer e-loyalty, addressing a gap in previous research. Using qualitative research and literature review, it analyzes the relationship between these variables. Findings reveal a significant positive effect of e-CRM and digital marketing on e-loyalty, emphasizing the importance of e-satisfaction. Suggestions for future research include incorporating additional factors like customer satisfaction and employing quantitative methods to strengthen findings. Expanding the scope to different industries beyond the ones studied could enhance understanding. Highlight: In-depth Analysis: Qualitative research explores e-CRM and digital marketing impact. Key Findings: Positive correlation found with customer e-loyalty, emphasizing e-satisfaction. Future Research: Suggested inclusion of more factors and quantitative methodologies. Keywoard: E-CRM, Digital Marketing, Customer E-loyalty, Qualitative Research, Literature Review